The Effect of Calcium Hydroxideon Mortality of Ascaridia galli In Vitro - Inggarsetya Syah Audini; Setiawan Koesdarto; Ira Sari Yudaniayanti; Setiawati Sigit; Sri Mumpuni Sosiawati; Agus Sunarso (Universitas Airlangga, 2018)
Ascaridiasis can be happened in either broiler or hens that can caused decrease of meat and egg productions. Ascaridiasis is a parasite that is most often found in poultry and cause high economic losses. This research was conducted to determine the anthelmintic effect of calcium hydroxide [Ca(OH)₂] on mortality of Ascaridia galli in vitro. In this research used Ascaridia galli with length 7-11 cm without differentiating their sex. The concentrations of calcium hydroxide [Ca(OH)₂] for immersion the Ascaridia galli were 0,01%, 0,02%, 0,025% and 0,03% as treatment group, respectively. The negative control used aquadest. Observation death A.galli worm and analysis of the data at the 2 hour, 4 hour, 6 hour, 8 hour, 10 hour and 12 hour. The result showed that the increase of concentration increased mortality of Ascaridia galli. Percentage of death worm A.galli at the 12th hour on concentration ,01%, 0,02%, 0,025% and 0,03% was 20%, 55%, 75% and 100%. ANOVA test showed significant difference between control and treatment group (p<0.05). Duncan multiple range test was seen the best treatment was the biggest mortality in concentration of 0,03%.